2015
DOI: 10.1590/s1980-65742015000100013
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent validation of the MABC-2 Motor Tests and MABC-2 Checklist according to the Developmental Coordination Disorder Questionnaire-BR

Abstract: The Movement Assessment Battery for Children, 2nd Ed (MABC-2), comprised of motor tests and a questionnaire (Checklist), has been used by several nationalities to identify problems in children's motor behavior. However, the level of agreement between the motor tests and the checklist has been questioned. So, this study aimed to test the level of competition between the MABC-2 motor test and MABC-2 Checklist, controlled by the Developmental Coordination Disorder Questionnaire (DCDQ-BR) as the gold reference. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 30 publications
(35 reference statements)
0
15
0
3
Order By: Relevance
“…Schoemaker et al 20 assessed children aged 5-8 years and found smaller albeit a signifi cant correlation between MABC and DCDQ (r= 0.36; p < 0.001). A smaller study of Brazilian children conducted by Capistrano et al 19 found no association between the instruments. These discrepancies may be related to methodological aspects, such as small group sizes.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Schoemaker et al 20 assessed children aged 5-8 years and found smaller albeit a signifi cant correlation between MABC and DCDQ (r= 0.36; p < 0.001). A smaller study of Brazilian children conducted by Capistrano et al 19 found no association between the instruments. These discrepancies may be related to methodological aspects, such as small group sizes.…”
Section: Discussionmentioning
confidence: 85%
“…However, other studies have shown larger differences regarding the prevalence of motor problems among children between the two instruments. Pannekoek et al 22 and Capistrano et al 19 suggested that this discrepancy can be explained due to methodological aspects used in the construction of the research tools 27 as well as varying cutoff points used to identify problems in different motor tests.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… Netelenbos [ 61 ] Strength: -Good reliability To be developed: -No sensitivity and specificity scores M-ABC-C / M-ABC-2-C UK 5.4–15.6 yrs. Capistrano et al [ 72 ]; De Milander [ 73 ]; Green et al [ 67 ]; Junaid et al [ 63 ]; Piek & Edwards [ 43 ]; Schoemaker et al [ 25 ]; Schoemaker et al [ 44 ]; Wright et al [ 45 ]; Wright & Sugden [ 74 ] Strengths: -Some good test–retest reliability scores -Translated in many countries To be developed: -Too long and time-consuming -Very low sensitivity: none of the studies met the required criteria -Inter-rater reliability not studied MOQ-T Netherlands 5–11 yrs. Asunta et al [ 41 ]; Giofre et al [ 42 ]; Schoemaker et al [ 62 ] Strengths: - Good construct validity - Sensitivity met the criteria - Good discriminant validity and concurrent validity - High internal consistency - Good sample sizes - Both population and clinical referred samples - Fast to fill, usability good To be developed: - Specificity is slightly too low - Inter-rater and test–retest reliability not studied TEAF Canada 6–11 yrs.…”
Section: Resultsmentioning
confidence: 99%